2002
DOI: 10.1002/cpp.339
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of emotion regulation in adolescents and young adults with substance dependence or eating disorders

Abstract: Some authors argue that both substance dependence and eating disorders should be considered as dependent behaviours. Similarities and differences between these disorders, however, remain unclear. This study compares processes of emotion regulation in adolescents and young adults (15 to 25 years old) with substance dependence (SD) or eating disorders (ED). One hundred and thirteen SD, 50 ED and 86 non-clinical subjects (NC), recruited in four French and Swiss locations, completed a self-report questionnaire of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
3
21
0
2
Order By: Relevance
“…Based on the CaMir, an individual exhibiting secure attachment values social support and relational security, a person with an avoidant attachment strategy values independence at the expense of social support, whereas a person with a preoccupied strategy values interpersonal involvement at the expense of autonomy (Pierrehumbert et al, 1996;Pierrehumbert et al, 2002). With the CaMir, the subject responds to each item twice.…”
Section: Assessment Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the CaMir, an individual exhibiting secure attachment values social support and relational security, a person with an avoidant attachment strategy values independence at the expense of social support, whereas a person with a preoccupied strategy values interpersonal involvement at the expense of autonomy (Pierrehumbert et al, 1996;Pierrehumbert et al, 2002). With the CaMir, the subject responds to each item twice.…”
Section: Assessment Instrumentsmentioning
confidence: 99%
“…The second distribution is used to calculate the attachment style. The Q-sort responses that are obtained for each participant are correlated with the three prototypes corresponding to the secure, avoidant, and preoccupied attachment styles and provide three correlation coefficients (Q indexes) that reflect the similarity of the individual"s answer to each of the three types of attachment (Pierrehumbert et al, 2002).…”
Section: Assessment Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Zonneville-Bender et al [23] confirmed this possible disconnection between the physiological and cognitive self-reported responses to emotional stimuli both in patients with anorexia and in alexithymic participants. In patients with anorexia, Pierrehumbert et al [24] observed a higher level of emotional physiological activation, whereas Zonnevylle-Bender et al [23] reported a discordance between self-reported emotional and neurophysiological arousal as measured by heart rate (HR) and cortisol levels during the psychosocial stress.…”
Section: Introductionmentioning
confidence: 98%
“…Recent models of eating disorders conceptualize EDBs as maladaptive coping mechanisms to attachment-related distress and negative emotions (Pierrehumbert et al, 2002;Luck et al, 2005;Smyth et al, 2007). Dietary restraint and physical exercise with the aim of body shaping are coping mechanisms for body dissatisfaction-related shame and negative self-esteem, which is correlated with insecure attachment in women with eating disorders (Troisi et al, 2006).…”
mentioning
confidence: 99%